Pathogenetic rationale for the use of immunomodulating and systemic enzyme therapy in treatment of nulliparous women with endometrioid ovary tumors - O S Shapoval; L L Vorontsova (Kazimierz Wielki University, 2015)
Shapoval O. S., Vorontsova L. L. Pathogenetic rationale for the use of immunomodulating and systemic enzyme therapy in treatment of nulliparous women with endometrioid ovary tumors = Патогенетическое обоснование применения иммуномодулирующей и системной энзимотерапии в комплексном лечении нерожавших женщин с опухолеподобными образованиями яичников. Journal of Education, Health and Sport. 2015;5(1):75-86. ISSN 2391-8306. DOI: 10.5281/zenodo.13992 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A75-86 https://pbn.nauka.gov.pl/works/527872 http://dx.doi.org/10.5281/zenodo.13992 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 05.10.2014. Accepted: 25.12.2014.   UDK 618.11 - 006.2:615.37 - 092] - 08 - 055.25 Pathogenetic rationale for the use of immunomodulating and systemic enzyme therapy in treatment of nulliparous women with endometrioid ovary tumors   Патогенетическое обоснование применения иммуномодулирующей и системной энзимотерапии в комплексном лечении нерожавших женщин с опухолеподобными образованиями яичников   O. S. Shapoval, L. L. Vorontsova О. С. Шаповал, Л. Л. Воронцова   State establishment «Zaporоzhye Medical Academy of Post-Graduate Education Ministry of Health of Ukraine», Zaporоzhye, Ukraine ГЗ «Запорожская медицинская академия последипломного образования МЗ Украины», Запорожье Department of Obstetrics and Gynaecology Department of Clinical Laboratory Diagnostics e-mail: shapoval_olga@ukr.net   Abstract The modern approach to the treatment options and assessment of its effectiveness in nulliparous women with endometrial cysts is build on optimal pathogenetically substantiated therapy based on features of the disease not only on the system, organ and tissue levels, and taking to consideration the cellular and molecular features of the functioning of the body. Therefore, the aim of our work was to determine the effectiveness of various treatment regimens for nulliparous women with ovary tumor-like formations based on features of the immune status. In the study of immune status in nulliparous women with endometrioid tumor-like formations of ovaries (n = 30) was the inconsistency of the phagocytic system, the imbalance of T- and B-cell immunity, dysimmunoglobulinemy. Based on the identification of changes, the patients were assigned with pathogenetically substantiated combination therapy that included, in addition to conventional treatment regimens, the appointment of immunomodulators and systemic enzyme therapy. Treatment results show the full normalization of phagocytic, T- and B-cells and partially humoral systems. Key-words: immunomodulating therapy, nulliparous women, tumor-like endometrioid ovarian formation.   Резюме Современный подход выбора варианта лечения и оценки его эффективности у нерожавших женщин с эндометриоидными кистами состоит в формировании оптимальной патогенетически обоснованной терапии с учетом особенностей заболевания не только на системном, органном и тканевом уровнях, а и с учетом клеточно-молекулярных особенностей функционирования организма. В связи с этим целью нашей работы являлось выявление эффективности применения различных схем лечения нерожавших женщин с опухолеподобными образованиями яичников с учетом особенностей иммунного статуса. При исследовании иммунного статуса у нерожавших женщин с опухолеподобными эндометриоидными образованиями яичников (n=30) была выявлена несостоятельность фагоцитарной системы, дисбаланс Т- и В-клеточного иммунитета, дизиммуноглобулинемия. основываясь на выявленных изменениях, пациенткам была назначена патогенетически обоснованная комбинированная терапия, включающая, помимо традиционной схемы лечения, назначение иммуномодуляторов и системной энзимотерапии. Результаты лечения свидетельствуют о полной нормализации показателей фагоцитарной, Т- и В-клеточной и, частично, гуморальной систем. Ключевые слова: иммуномодулирующая терапия, нерожавшие женщины, опухолеподобные эндометриоидные образования яичников.